Formal Modeling and Verification for MVB - Mo Xia; Kueiming Lo; Shuangjia Shao; Mian Sun (Journal of Applied Mathematics)
Multifunction Vehicle Bus (MVB) is a critical component in the Train Communication Network (TCN), which is widely used in most of the modern train techniques of the transportation system. How to ensure security of MVB has become an important issue. Traditional testing could not ensure the system correctness. The MVB system modeling and verification are concerned in this paper. Petri Net and model checking methods are used to verify the MVB system. A Hierarchy Colored Petri Net (HCPN) approach is presented to model and simulate the Master Transfer protocol of MVB. Synchronous and asynchronous methods are proposed to describe the entities and communication environment. Automata model of the Master Transfer protocol is designed. Based on our model checking platform M3C, the Master Transfer protocol of the MVB is verified and some system logic critical errors are found. Experimental results show the efficiency of our methods.